Evaluation of general anesthesia induced by propofol, ketamine protocol in rabbits premedicated with diazepam: Ayad A. Amin and Areej Ali Atiyah - Atiyah, Areej Ali (The Iraqi Journal of Veterinary Medicine, 2014)
The present study was designed to evaluate the efficacy of diazepam-propofol-Ketamine protocol for induction of general anaesthesia in rabbits. The experiment was conducted on seventeen healthy male adult local rabbits weighting 0.9-1.5 kg. Rabbits were given protocol, Diazepam 1mg/kg B.W. by intramuscular injection then 15 minutes later propofol 10 mg/kg B.W. as bolus slow intravenous injection and ketamine 25 mg/kg BW by intramuscular injection. Several parameters included respiratory rate, body temperature and heart rate were recorded before injection of drugs and after giving the anesthetic protocol at 0, 5, 10, 15, 20, 30, 45, 60, 75 and 90 minutes. The results showed that the anaesthesia with diazepam, propofol and Ketamine protocol in rabbits was suitable as it produced reliable surgical anaesthesia, good analgesia and muscle relaxation with minimal changes on the wave morphology of the cardiac muscle.